METHODS OF FORMATION OF PROFESSIONAL COMPETENCE OF STUDENTS ON THE BASIS OF AN INNOVATIVE APPROACH - Karimova Feruza Hamidorovna; Xakimova Muxabbat Fayziyevna (Galaxy International Interdisciplinary Research Journal, 2022)
This study considers the introduction of a systematic approach in the training of higher education specialists, which effectively leads to the formation of their professional competence. The results of the study of professional difficulties of teachers of higher educational institutions in interaction with participants in the educational process are presented. The technology of training based on a systematic approach creates conditions for the systematic organization of the activities of participants in the learning process, as well as for the development of systems thinking skills and a systematic approach in cognitive, practical and other current and upcoming events. An important factor in the formation of the professional competence of future specialists is the formation of an indicative basis for their future professional activities. The characteristic of the structure and components of professional competence is given. Examples demonstrating the implementation of the formation of professional competencies with an emphasis on the current needs of society are also presented. A description of a significant increase in the professional competence of students after the correction of the methods of its formation is given.